2005
DOI: 10.1128/jb.187.23.8127-8136.2005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of New Thiamine-Deregulated Mutants of Bacillus subtilis

Abstract: In bacteria, thiamine pyrophosphate (TPP) is an essential cofactor that is synthesized de novo. Thiamine, however, is not an intermediate in the biosynthetic pathway but is salvaged from the environment and phosphorylated to TPP. We have isolated and characterized new mutants of Bacillus subtilis that deregulate thiamine biosynthesis and affect the export of thiamine products from the cell. Deletion of the ydiA gene, which shows significant similarity to the thiamine monophosphate kinase gene of Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…In agreement with other groups, we propose the name "ThiT" for Lmo1429 and its homologs such as YuaJ of B. subtilis (8,31). Growth in the presence of pyrithiamine.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…In agreement with other groups, we propose the name "ThiT" for Lmo1429 and its homologs such as YuaJ of B. subtilis (8,31). Growth in the presence of pyrithiamine.…”
Section: Resultssupporting
confidence: 50%
“…(for example Bacillus weihenstephanensis: 43% identity and 65% similarity over a length of 185 aa and E value of 10 Ϫ38 ) and also those of Streptococcus spp., Lactobacillus spp., or Enterococcus faecalis. The genome of L. monocytogenes does not contain genes with sequence similarities to the presumably thiamine precursor-specific ABC transporter encoded by the ykoFEDC (thiUVWX) operon of B. subtilis (31). To provide experimental evidence for the thiamine transport activity of Lmo1429, we constructed the deletion mutant EGD⌬thiT.…”
Section: Resultsmentioning
confidence: 99%
“…The YkoEDC system was predicted to be involved in salvaging the thiamine precursor hydroxymethylpyrimidine, based on the positional clustering of the ykoEDC cassette with the thiaminase II gene tenA, and some other thiamine salvage genes (34). Genetic and microarray studies of B. subtilis mutants in the thiT and ykoD genes demonstrated that both mutations result in a derepression of thiamine-regulated genes, confirming the involvement of thiT and ykoEDC in the uptake of thiamine and its precursors (38). The thiamine-related transporter ThiW was predicted to be involved in the uptake of the thiazole precursor of thiamine based on the colocalization of the thiW with thiM genes, with the latter encoding the thiazole salvage enzyme hydroxyethylthiazole kinase (34).…”
Section: Resultsmentioning
confidence: 95%
“…Membrane proteins of unknown function whose genes are associated with the TPP riboswitch have subsequently been shown to be involved with TPP and thiamin transport (Rodionov et al 2002;Winkler et al 2002;Schyns et al 2005), illustrating how characterization of RNA genetic control elements can lead toward description of protein function. Likewise, knowledge of the function of a protein encoded by an mRNA can aid in establishing the ligand identity of an associated riboswitch.…”
Section: Discussionmentioning
confidence: 99%